Концепция о правителе в философии аль-Фараби (Journal of Philosophy Culture and Political Science, 2020)
The article is devoted to the concept of the Ruler in the philosophy of al-Farabi. The Thinker arguesthat the Ruler of a virtuous city must be both an “imam”, a “philosopher” (scientist), because only theyare gifted people who are called to rule society.The ruler, according to al-Farabi, is a chosen person with a special intellect and wonderful humanqualities. As a scientist, he is not limited to simple common knowledge about the people. Also, the rulershould be able to figuratively convey in words his knowledge and guide the inhabitants of the city tohappiness. To this end, he believes that the true Ruler should be concerned about one thing – this isconcern for the inhabitants of the city for many years. The pratitel in the philosophy of al-Farabi has innatequalities, such as love of truth, justice, selfless fulfillment of good, honor, hatred of lies, contemptfor flattery, etc.Al-Farabi’s first leadership can be achieved in the following ways: first in man there is a sublimeintellect, then in him there is a progressive intellect, and then, as described in Aristotle’s book On theSoul, there is an active intellect. Such a person was called a real akim by the ancients.According to the authors, the logic of a happy society, which al-Farabi so craved, lies in the art ofmanagement, knowledge and methods, about which so much is said in his works. The image of a scientistleader is an example. As before, it is tirelessly necessary to improve public administration, the systemof power, and instill good in members of society.Key words: Al-Farabi, first leader, society, happiness, philosopher.